Sports Practice, Body Image Perception, and Factors Involved in Sporting Activity in Italian Schoolchildren - Luciana Zaccagni; Luca Rosa; Stefania Toselli; Emanuela Gualdi-Russo (MDPI AG, 2023)
Regular physical activity is generally deemed to positively affect health, but studies on children are scarce. Among the kinds of physical activity, sports practice is the most common and easiest to quantify and report by children. This cross-sectional study aimed to compare the two genders and evaluate the association between organized sports practice and body dissatisfaction in a sample of 214 Italian schoolchildren (55.6% males) aged 5 to 12. Body image perception and data on sports practice expectations and facilitators were collected in individual face-to-face interviews; weight and stature were directly measured. Girls tended to be sportier than boys (91.6% of girls vs. 86.3% of boys practiced sports), with an earlier start in sports (5.48 ± 1.47 vs. 5.72 ± 1.38 years) and a greater amount of weekly sports (3.41 ± 2.95 vs. 3.01 ± 2.11 h/week). In both genders, the ideal silhouette was more slender than the feel silhouette, and in girls more than in boys. According to the outcomes of multiple regression models, years of organized sports participation were a significant predictor of the weekly amount of sports in both genders, in addition to the feel weight status minus actual weight status inconsistency score, fun in sports, and parental support only in boys and teacher support only in girls. Children's needs and interests and sports facilitators should be considered to promote an early active lifestyle.